Soil Surface-Trapping of Tomato Leaf-Miner Flies Emerging from Underground Pupae with a Simple Electrostatic Cover of Seedbeds in a Greenhouse - Teruo Nonomura; Hideyoshi Toyoda (Insects, 2020)
In the present study, an electrostatic apparatus for trapping adult tomato leaf miner flies (Liriomyza sativae) emerging from underground pupae at the surface of a seedbed in an organic greenhouse was developed. The apparatus consisted of insulated iron rods arranged in parallel at set intervals and linked to a voltage generator, which supplied a negative charge to the rods, as well as non-insulated grounded iron rods with the same configuration. The two layers of insulated and non-insulated iron rods were arrayed in parallel to form a static electric field between the layers. The electric field created a strong attractive force capable of capturing flies that entered the field. In a greenhouse assay, the apparatus was placed horizontally above a seedbed in a greenhouse and surveyed for its ability to capture adult flies emerging from pupae that were introduced onto the seedbed beneath the apparatus. The results revealed that the apparatus effectively trapped all adult flies that emerged from the pupae and that it functioned stably while continuously operated during the entire period of the experiment. Thus, our novel apparatus is a promising tool for the physical control of adult tomato leaf miners in the insecticide-independent cultivation of greenhouse tomatoes.